Violencia política, paz social y derecho - Del Picó Rubio, Jorge (Pontificia Universidad Católica del Perú, 2024)
This article puts forward a contemporary reflection about violence based on a finalist legal assessment of peace. For that purpose, it both distinguishes and relates these two concepts, particularly regarding their politically motivated expressions, as well as it highlights the functionality of law to achieve negative peace and the ensuing morality of positive peace. In doing so, it considers the works written on this subject by influential contemporary authors as a reference point, after which it projects a legal perspective on violence through the analysis of three dimensions of this phenomenon that rely on categories both of legal theory and legal philosophy. This paper concludes that the final motivations that bring about conflict among States, groups and individuals admit similarities among themselves when they are pushed to the maximum level of incivility and irrationality. Likewise, it states that the distinction between law and morality is used improperly by those who use violence as a method for political action because they pretend to justify their actions therein as a way to ignore or evade their being as subjects ruled by the law.

Este artículo propone una reflexión contemporánea acerca de la violencia basada en una evaluación jurídica finalista de la paz. Para estos efectos, distingue y relaciona estos dos conceptos, particularmente respecto de sus expresiones políticamente motivadas, así como destaca la funcionalidad del derecho para conseguir paz negativa y la consiguiente moralidad de la paz positiva. Al proceder de esta forma, considera los trabajos escritos por autores contemporáneos influyentes como referencia, después de lo cual proyecta una perspectiva legal sobre la violencia a través del análisis de tres dimensiones de este fenómeno que descansan en categorías de la teoría del derecho y la filosofía jurídica. Este trabajo concluye que las motivaciones finalistas que producen conflicto entre Estados, grupos e individuos admiten similitudes entre ellas mismas cuando son empujadas al máximo nivel de incivilidad e irracionalidad. Del mismo modo, afirma que la distinción entre derecho y moral es utilizada impropiamente por quienes usan la violencia como método para la acción política porque pretenden justificar sus acciones en ella para desconocer o evadir su ser como sujetos gobernados por el derecho.
Keywords: Political violence; Social peace; Purposes of the law; War; Philosophy of law; Violencia política; Paz social; Fines del derecho; Guerra; Filosofía del derecho; https://purl.org/pe-repo/ocde/ford#5.05.01